High quality colonoscopy: using textbook process as a composite quality measure - Nass, Karlijn J.; van Doorn, Sascha C.; Fockens, Paul; Rees, Colin J.; Pellisé, Maria; van der Vlugt, Manon; Dekker, Evelien (Endoscopy, 2023)
Background High quality colonoscopy is fundamental to good patient outcomes. “Textbook outcome” has proven to be a feasible multidimensional measure for quality assurance between surgical centers. In this study, we sought to establish the “textbook process” (TP) as a new composite measure for the optimal colonoscopy process and assessed how frequently TP was attained in clinical practice and the variation in TP between endoscopists.Methods To reach consensus on the definition of TP, international expert endoscopists completed a modified Delphi consensus process. The achievement of TP was then applied to clinical practice. Prospectively collected data in two endoscopy services were retrospectively evaluated. Data on colonoscopies performed for symptoms or surveillance between 1 January 2018 and 1 August 2021 were analyzed.Results The Delphi consensus process was completed by 20 of 27 invited experts (74.1 %). TP was defined as a colonoscopy fulfilling the following items: explicit colonoscopy indication; successful cecal intubation; adequate bowel preparation; adequate withdrawal time; acceptable patient comfort score; provision of post-polypectomy surveillance recommendations in line with guidelines; and the absence of the use of reversal agents, early adverse events, readmission, and mortality. In the two endoscopy services studied, TP was achieved in 5962/8227 colonoscopies (72.5 %). Of 48 endoscopists performing colonoscopy, attainment of TP varied significantly, ranging per endoscopist from 41.0 % to 89.1 %.Conclusion This study proposes a new composite measure for colonoscopy, namely “textbook process.” TP gives a comprehensive summary of performance and demonstrates significant variation between endoscopists, illustrating the potential benefit of TP as a measure in future quality assessment programs.